Implementation of the WASAKA Learning Model on the Topic of Heat and Temperature - Lutfiyanti Fitriah; Ana Widya Ilahi; Masniah Masniah; Muhammad Akhsan Arif; Fahmi Yahya (Universitas Lambung Mangkurat, 2024)
This research aims to delineate the implementation of the WASAKA learning model and describe students' responses to this learning model through a one-to-one test. This study employed the Educational Design Research (EDR) methodology, encompassing two stages: the preliminary stage and the formative evaluation stage. Ten students participated in a one-to-one test during a single meeting, focusing on learning heat and temperature topics in the Fundamental Physics lecture. Research instruments included observation sheets and response questionnaires, with data analyzed using descriptive statistics. The results of the data analysis revealed an average score of 5.00 for implementing the WASAKA learning model, categorizing it as